PENINGKATAN PENGETAHUAN PETERNAK TENTANG SUPLEMEN HERBAL DI KECAMATAN CAMPALAGIAN KABUPATEN POLEWALI MANDAR - Pratiwi, Nita Adillah Pratiwi; Fahrodi, Deka Uli; HM, Rahmaniah; Yosua, Yosua; Andika, Andika (Jurnal Abdi Insani, 2024)
Katumbangan Village is one of the villages in Campalagian Subdistrict that has soil fertility and a good rainfall climate supported by evenly distributed plant vegetation growth, making places like this very suitable for beef cattle farming. One of the innovations given to farmers in the prevention and handling of diseases is by providing herbal supplements as additional feed for livestock. Herbal supplements are a type of additional supplement given to livestock whose basic ingredients are made from herbs and spices.  The socialisation and demonstration activities on making and giving herbal supplements to ruminants are expected to make it easier for farmers to handle and prevent diseases in livestock through herbal supplements. The methods provided consist of: 1. socialisation or presentation of material on efforts to handle and prevent diseases through herbal supplements. 2. training and technology application is a hands-on demonstration on making herbal supplements. 3. monitoring and evaluation through pretest and posttest. The results of the implementation of community service increased the knowledge of farmers about the types of diseases, handling and prevention of diseases before training only 12% and after training there was an increase of 91%. Meanwhile, farmers' knowledge of herbal supplements before the community service activities from not knowing to 95%. In addition, there was an increase in farmers' knowledge about kitchen spice ingredients that can be used as herbal supplements for livestock. The use of herbal supplements to reduce the use of antibiotics that can cause resistance. This activity went very well as evidenced by starting from the socialization of farmers actively involved, training activities farmers also actively helped in making herbal supplements and there was an increase in knowledge from before the activity and after the activity.